2003
DOI: 10.1046/j.1365-2249.2003.02114.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered CD8+ T cell responses to selected Epstein–Barr virus immunodominant epitopes in patients with multiple sclerosis

Abstract: SUMMARYAn increased frequency of antiviral CD8 + T cells is seen in chronic viral infections. During herpes virus infections the expanded CD8 + T cells are thought to control the reactivation of the latent infection. Because multiple sclerosis (MS), a presumed autoimmune disease of the central nervous system, has been associated with a late Epstein-Barr virus (EBV) infection, we wished to examine whether the CD8 + T cell response to EBV epitopes differed between MS patients and healthy controls. Here we report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 42 publications
1
69
0
1
Order By: Relevance
“…With regard to the environmental factors, sero-epidemiological studies revealed that the g-herpesvirus EBV was associated with MS (5,6). We and other investigators demonstrated that EBV-specific cellular immune responses are increased not only in the blood (7)(8)(9)(10) but also in the cerebrospinal fluid of MS patients (11). Interestingly, we showed that the increase in EBV-specific CD8 + T cell response was maximal at disease onset but decreased with disease duration (9).…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…With regard to the environmental factors, sero-epidemiological studies revealed that the g-herpesvirus EBV was associated with MS (5,6). We and other investigators demonstrated that EBV-specific cellular immune responses are increased not only in the blood (7)(8)(9)(10) but also in the cerebrospinal fluid of MS patients (11). Interestingly, we showed that the increase in EBV-specific CD8 + T cell response was maximal at disease onset but decreased with disease duration (9).…”
mentioning
confidence: 52%
“…However, the magnitude of the CD8 + T cell response in MS patients is significantly lower for the HLA-B7/CMV TPR epitope and tends to be lower for the HLA-B7/ EBV RPP epitope. With regard to the CD8 + T cell responses against the latter, other investigators found either no difference between MS patients and control subjects (37) or an increased magnitude of HLA-B7/EBV RPP -specific CD8 + T cells in MS patients (8), as reflected by the secretion of IFN-g in an ELISPOT assay. However, a direct comparison is difficult, because the data on the magnitude of tetramer + cells were obtained by gating on CD3 + and CD8 + T cells, whereas the ELISPOT assays were performed on total unfractionated PBMC.…”
Section: Discussionmentioning
confidence: 99%
“…Among the latter, the g-herpesvirus EBV has been repeatedly associated with this disease [2][3][4]. Large seroepidemiological studies [5][6][7][8] and cellular immune response assessments [9][10][11][12] have demonstrated enhanced EBV-specific immune responses in the blood of MS patients.…”
Section: Introductionmentioning
confidence: 99%
“…One possible mechanism for this is decreased MHC class I expression on B cells, which has been reported to occur in patients with MS [36] and other autoimmune diseases [37], although it remains unclear whether the reported decrease is sufficient to cause decreased EBV-specific CD8+ T-cell cytotoxicity. A recent study found an increased frequency of CD8+ T cells responding to two immunodominant EBV epitopes in MS patients but it was not determined whether these T cells were cytotoxic [38]. EBV-specific CD8+ T cells are enriched in MS brain lesions compared to the peripheral blood, but such enrichment is also found for EBV-specific and cytomegalovirus-specific CD8+ T cells in other inflammatory lesions of the brain and other organs, including non-autoimmune inflammatory lesions [39].…”
Section: Multiple Sclerosis (Ms)mentioning
confidence: 99%